Faktor-Faktor yang Mempengaruhi Kepatuhan Protokol Kesehatan pada Masa Tatanan Baru di Kecamatan Sukarame Kota Bandar Lampung - Prihantoro Prihantoro; Lolita Sary; Fitri Ekasari; Khoidar Amirus (Universitas Malahayati Lampung, 2022)
ABSTRACT: FACTORS AFFECTING HEALTH PROTOCOL COMPLIANCE WHEN NEW ORDER IN BANDAR LAMPUNG Introduction: The Covid-19 pandemic shows cases that continue to increase, especially in the Sukarame District area. But on the other hand, public awareness in implementing health protocols is still low.Objective: The purpose of this study was to determine the factors that influence compliance with health protocols during the New Order era in Sukarame District, Bandar Lampung City in 2021.Methods: This type of research is quantitative, with a cross sectional design. The research was conducted in Sukarame District, Bandar Lampung City. The number of population and sample was determined based on accidental sampling so that the sample obtained in this study amounted to 97 respondents. The data analysis techniques used were univariate, bivariate (chi-square), and multivariate (multiple logistic regression). Results: The results showed that there was an effect of perceived vulnerability (pv=0.001), perceived severity (pv=0.022), perceived barriers (pv=0.034), and perceived benefits (pv=0.018) on adherence to health protocols during the New Order in the District. Sukarame City of Bandar Lampung.Conclusion: This study suggests optimizing the program and minimizing misinformation about covid-19 at the local, cluster level by using pamphlets, banners, posters, or direct outreach media. Provide proper education about Covid-19 and equip officers with basic communication skills. Keywords: Covid-19, severity perception, vulnerability, benefits, and barriers INTISARI: FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN PROTOKOL KESEHATAN PADA MASA TATANAN BARU DI BANDAR LAMPUNG Pendahuluan: Pandemi Covid-19 menunjukkan kasus yang terus meningkat khususnya di wilayah Kecamatan Sukarame. Namun di sisi lain kesadaran masyarakat dalam penerapan protokol kesehatan masih rendah.Tujuan: Tujuan Penelitian ini adalah diketahuinya faktor faktor yang mempengaruhi kepatuhan protokol kesehatan pada masa tatanan baru di Kecamatan Sukarame Kota Bandar Lampung tahun 2021.Metode: Jenis penelitian kuantitatif, dengan desain crossectional. Penelitian dilakukan di Kecamatan Sukarame Kota Bandar Lampung. Jumlah populasi dan sampel ditentukan berdasarkan accidental sampling sehingga diperoleh sampel pada penelitian berjumlah 97 responden. Teknik analisis data yang digunakan adalah univariat, bivariat (chisquare) dan multivariat (regresi logistik berganda) Hasil: Hasil penelitian menunjukkan adanya pengaruh persepsi kerentanan (pv=0,001), persepsi keparahan (pv=0,022), persepsi hambatan (pv=0,034) dan persepsi manfaat (pv=0,018) terhadap kepatuhan protokol kesehatan pada masa tatanan baru di kecamatan Sukarame Kota Bandar Lampung.Kesimpulan: Penelitian ini menyarankan agar mengoptimalkan program dan meminimalisisr informasi tidak benar tentang covid-19 di tingkat lokal, cluster dengan menggunakan media pamflet, spanduk, poster atau penyuluhan langsung. Memberikan edukasi benar seputar Covid-19 dan membekali petugas dengan keterampilan dasar komunikasi. Kata Kunci: Covid-19, persepsi keparahan, kerentanan, manfaat dan hambatan.